2004
DOI: 10.1002/jat.955
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of sulfur mustard skin injury following a topical treatment with a mixture of a steroid and a NSAID

Abstract: The ability to ameliorate sulfur mustard (HD)-induced oedema by treatment with anti-inflammatory drugs was reported previously after screening four steroids and four non-steroidal anti-inflammatory drugs (NSAIDs) using the mouse ear vesicant model. Following the screening study, one steroid and one NSAID (Adexone and Voltaren) were selected as the most effective, and a mixture of the two was chosen for the present more extensive research. The effect of the combined treatment on clinical, biochemical and histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…It remains to be determined if the combined use of these compounds with protease inhibitors would be useful adjunct to HD therapy, though Cowan et al (2003) refer to such inhibitors as ethyl p-guanidino benzoate HCl as having potential utility. It is generally the case that anti-inflammatory compounds are more effective in in vivo models than other classes of candidate countermeasures, though such treatments do not prevent epithelial cell death occurring in the skin following exposure to HD (Dachir et al, 2004). This is a finding supported in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…It remains to be determined if the combined use of these compounds with protease inhibitors would be useful adjunct to HD therapy, though Cowan et al (2003) refer to such inhibitors as ethyl p-guanidino benzoate HCl as having potential utility. It is generally the case that anti-inflammatory compounds are more effective in in vivo models than other classes of candidate countermeasures, though such treatments do not prevent epithelial cell death occurring in the skin following exposure to HD (Dachir et al, 2004). This is a finding supported in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Early studies with the SM analogs 2-chloroethyl ethyl sulfide (CEES) and NM from our laboratory and elsewhere have shown that pathways related to DNA damage, oxidative stress and inflammation are involved in their skin injury effects (Sabourin et al , 2002; Kehe et al , 2009; Pal et al , 2009; Tewari-Singh et al , 2010; Inturi et al , 2011; Jain et al , 2011a; Jain et al , 2011b). Accordingly, both antioxidants, such as AEOL10150, glutathione, sulforaphane, butylated hyroxyanisole, ebselen and others (Paromov et al , 2007; Laskin et al , 2010; Tewari-Singh et al , 2011; Tewari-Singh et al , 2014a) and anti-inflammatory drugs (Nyska et al , 2001; Dachir et al , 2004; Chang et al , 2014) have been evaluated to treat vesicant-induced skin injuries and have shown some promise. However, more efforts are needed to identify novel agents to rescue vesicants-induced skin injuries, specifically in the mass causality scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Topical silver sulfadiazine can be applied to all burns, and an Elizabethan collar should be put in place to decrease ingestion of the ointment and self-trauma. Topically applied dexamethasone and diclofenac reduced inflammation in a mouse when applied within 4 h (Dachir et al, 2004). All equine and ovine patients should be inoculated with tetanus toxoid.…”
Section: Decontamination and Treatmentmentioning
confidence: 99%